Muhammad and the Believers at the Origins of Islam: By Fred M. Donner (Cambridge, MA, Harvard University Press, 2010, hbk., 280 pages) (American Journal of Islam and Society, 2011)
Fred Donner’s Muhammad and the Believer’s at the Origins of Islam is themost recent in a long line of books that have attempted to recast the narrativeof the early history of Islam in ways that seek to challenge both traditionalIslamic readings of the sources and previous academic scholarship.Donner explicitly states that his book has two goals. The first is to challengethe notion that he sees as permeating Western scholarship on Islam: that theProphet Muhammad (ṢAAS) and his followers were mainly motivated byfactors other than religion ‒ that is to say, that Islam was more of a politicalmovement than a religious one. On this point, Donner argues persuasivelythat the primary motivation guiding the Prophet and his movement wasreligious and that his message was a clarion call to monotheism and piety that built upon Christianity and Judaism. More controversially, Donner arguesthat the Prophet Muhammad was less the founder of a new religiouscommunity than “an inspired visionary” who “inaugurated a pietistic religiousmovement that we can best call, followings its adherents own usage,the Believers movement (86‒87).” This movement was not in its originsa new religion but instead an ecumenical community, which included notonly Arabs newly converted to monotheism but also Christians and Jews.Donner’s second task is to counter the notion that that the Umayyads were“cynical manipulators of the outward trappings of the religious movementbegun by Muhammad (xii).” Instead, Donner seeks to rehabilitates theUmayyads “as rulers who sought practical ways to realize the most importantgoals of the movement and perhaps more than anyone else helpedthe Believers attain a clear sense of their own distinct identity and of theirlegitimacy as a religious community (xii).” ...